-2(3y-1)-x=0

Simple and best practice solution for -2(3y-1)-x=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2(3y-1)-x=0 equation:


Simplifying
-2(3y + -1) + -1x = 0

Reorder the terms:
-2(-1 + 3y) + -1x = 0
(-1 * -2 + 3y * -2) + -1x = 0
(2 + -6y) + -1x = 0

Reorder the terms:
2 + -1x + -6y = 0

Solving
2 + -1x + -6y = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-2' to each side of the equation.
2 + -1x + -2 + -6y = 0 + -2

Reorder the terms:
2 + -2 + -1x + -6y = 0 + -2

Combine like terms: 2 + -2 = 0
0 + -1x + -6y = 0 + -2
-1x + -6y = 0 + -2

Combine like terms: 0 + -2 = -2
-1x + -6y = -2

Add '6y' to each side of the equation.
-1x + -6y + 6y = -2 + 6y

Combine like terms: -6y + 6y = 0
-1x + 0 = -2 + 6y
-1x = -2 + 6y

Divide each side by '-1'.
x = 2 + -6y

Simplifying
x = 2 + -6y

See similar equations:

| x^3=-10x^2-24x | | 24(y+2)=45 | | 7r-30=5 | | 96+2a=a+101 | | 8x+(3+7x)= | | 8c+(7-9c)= | | x^2-2x=80 | | x^2+34x=0 | | 9c=36 | | 0.5x+0.4(20)=0.3(x+30) | | x^2+50x=0 | | -2a+3+3a=11-20 | | w-4w+20=-8 | | x(x+7)=-12 | | 3(x+1)-1=3x+2 | | 3x^2-13x=-4 | | x^2+48=0 | | 5(5y-2)-4(4y-3)=y | | 2x(x+6)-10=55 | | 2(2w+8)+2w=76 | | 8y+3y+36=124 | | 4k=16 | | 7(b+3)=4b+2 | | w^2-3w=0 | | 8=4v+13 | | 7(b+3)=13b+2 | | x=3y-27 | | 10x^2+17x+7= | | n+n=20 | | 1.3(X+5)=10 | | 3n+2n=20 | | 6z+28=12z+10 |

Equations solver categories